(untitled) (AYUSHDHARA, 2024)
Trigeminal Neuralgia (TN) is a neuropathic pain syndrome which is characterized by critical unilateral paroxysmal facial pain. TN is a chronic pain disorder that affects the trigeminal nerve Attacks of pain are usually stimulated by tactile irritation within the part of the trigeminal nerve. TN leads with disability and poor quality of life, even when patients are taking conventionally treatments. Case- A 71 years old man consulted in Out-patient department of Sanjeevani Hospital, DSRRAU, Jodhpur, with the complains of sudden pain like electric shock on right side of the head which gets aggravated on touch patient and so MRI was done which was suggestive of patient suffering with trigeminal neuralgia. In the present case report patient was considered suffering from Anantvata and was treated with 2 sittings of leech therapy with oral medications like Ekangveer Ras, Mahavatavidhvansan ras, a mixture of Ashwagandha Churna, Bala churna, Godanti bhasma and Dashmool kwath with Anutaila Nasya, were also added to the treatment and the same continued for three months. According to symptoms, patient was diagnosed with TN. As per the outcomes, we can say that the cases of TN can be successfully managed with Ayurvedic treatment only and no surgical intervention is needed.